2009
DOI: 10.1016/j.ejpain.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and dry needling in the management of myofascial trigger point pain: A systematic review and meta‐analysis of randomised controlled trials

Abstract: Pain from myofascial trigger points is often treated by needling, with or without injection, although evidence is inconclusive on whether this is effective. We aimed to review the current evidence on needling without injection, by conducting a systematic literature review. We searched electronic databases to identify relevant randomised controlled trials, and included studies where at least one group were treated by needling directly into the myofascial trigger points, and where the control was either no treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
155
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(163 citation statements)
references
References 40 publications
5
155
0
3
Order By: Relevance
“…10,23,24 Cum-mings and White, 10 in their systematic review of 23 RCTs of needling therapies (dry needling or injections), stated that direct needling of MTrPs seems to be an effective treatment, but the hypothesis that needling therapies have efficacy beyond placebo is neither supported nor refuted by the evidence from clinical trials. Any effect of these therapies is probably because of the needle or placebo rather than the injection of either saline or active drug.…”
Section: Effectiveness Of Dry Needling In the Management Of Mtrpsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,23,24 Cum-mings and White, 10 in their systematic review of 23 RCTs of needling therapies (dry needling or injections), stated that direct needling of MTrPs seems to be an effective treatment, but the hypothesis that needling therapies have efficacy beyond placebo is neither supported nor refuted by the evidence from clinical trials. Any effect of these therapies is probably because of the needle or placebo rather than the injection of either saline or active drug.…”
Section: Effectiveness Of Dry Needling In the Management Of Mtrpsmentioning
confidence: 99%
“…Two studies provided contradictory results when comparing direct needling of MTrPs versus needling elsewhere in muscle; the evidence from another 4 studies failed to show that needling directly into an MTrP is superior to various nonpenetrating sham interventions. Tough and colleagues 24 mentioned significant methodological limitations of original studies included in the review. Firstly, although MTrPs seem to have been identified carefully in most studies, it is not clear that they were the sole cause of pain.…”
Section: Effectiveness Of Dry Needling In the Management Of Mtrpsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous review of seven studies noted limited evidence of dry needling on MTP, and a meta-analysis concluded that this technique is not superior to placebo. [9] In another study, 39 elderly patients complaining of myofascial pain in the trapezius muscle were randomly divided into two groups; significant improvements in pain were observed after 4 weeks, but there was no significant difference between groups. [10] Shoulder pain of different etiologies may respond to a single IA or subacromial CS injection.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments of MTrP include manual therapies [1], physical therapy modalities [25], needling therapy (including MTrP injection [26], dry needling [27][28][29], acupuncture [30][31][32], percutaneous soft tissue release [33], and subcutaneous needling [34]), or oral medicine. Eliminating any perpetuating factors and introducing adequate education and home programs to patients are also important [1,35].…”
Section: Treatment Of Myofascial Trigger Pointmentioning
confidence: 99%